AWARENESS ABOUT INTRATHECAL DRUG ADMINISTRATION AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Intrathecal administration includes the immediate infusion of the medication in cerebrospinal fluid (CSF) internal to the intrathecal space of the spinal column. The intrathecal course permits direct medication delivery to the CSF by evading the blood-cerebrum hindrance. It permits conveyance of small medication dosages, and the event of adverse effects is decreased compared with systemic courses of medication administration. This survey was performed for assessing the awareness about intrathecal drug administration among dental students. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about intrathecal drug delivery in medical applications, their medicinal uses, drugs administered, mechanism of action, and side effects. The responses were recorded and analyzed. 17% of the respondents were aware of medical uses of intrathecal drug delivery; 13% were aware of the drugs used in intrathecal drug delivery . 10 % were aware of the mechanism of action of intrathecal drug delivery . 7% were aware of side effects of intrathecal drug delivery . The awareness about intrathecal drug administration among dental students is not adequate. Increased awareness programs and continuing dental education programs in intrathecal drug delivery should be initiated to improve the awareness levels.